Finfish And Shellfish Diversity of Poonthura Estuary -Spatial And Temporal Variations in Accordance With Environmental Signatures - Kiranya, B. (Dept.of Fisheries Resource Management, 2017)
Abstract- Poonthura estuary located in Thiruvananthapuram district is a highly polluted sand bar estuary providing livelihood support to fishermen of adjacent areas including migrants and part time fishermen. In view of the scanty information on this estuary, an attempt was made to investigate the fish and shellfish biodiversity of the estuary and to study the seasonal changes in major physico-chemical parameters that have major roles in regulating the fauna inhabiting it. Following a preliminary survey, three stations were fixed for collection of monthly samples of fish and shellfish using gill net and cast nets for biodiversity studies and seasonal samples of water for assessment of environmental parameters. A total of 51 species, comprising 46 finfishes and 5 shellfishes belonging to 8 orders and 30 families were recorded based on which a checklist along with IUCN status was prepared. Values of biodiversity indices such as Margalef’s Richness Index, Pielou’s Evenness Index (J), Shannon Diversity Index (loge2), Simpson Diversity Index (1-λ), Simpson Dominance Index (λ), Average Taxonomic Distinctness (△+) and Variation in Taxonomic Distinctness (λ+) were worked with gill net and cast net samples separately for monthly data, seasonal data and station wise data. Based on cluster analysis, four clusters showing 40 % similarity were formed in the case of gill net samples and 20 % similarity in the case of cast net samples. Seasonal observations of gill net samples showed that the highest number of species were recorded during post-monsoon with 32 species whereas, cast net samples showed highest number of species during monsoon with 15 species. Observations on station wise diversity revealed that highest number of species were recorded from station-3 with 36 species from gill net catches whereas equal number of species were recorded from station-1 and station-3 from cast net catches. Analysis of various physico-chemical parameters showed that seasonal and spatial fluctuations in their values were influenced by a variety of extrinsic factors including seasons, river run off, sewage discharge and intrusion of saline water. Spatial and temporal data of primary productivity showed that post-monsoon season had the maximum productivity associated with higher nutrients following monsoon and river run off. Proper management inputs are necessary to sustain the resources along with pollution abatement measures for improving the livelihood support from this estuary.